Answer: a) -6, b) 32, c) -48, d) 9, e) -12
Explanation:
Since we have given that
A and B are 4 × 4 matrices.
Here,
det (A) = -3
det (B) = 2
We need to find the respective parts:
a) det (AB)
![\mid AB\mid=\mid A\mid.\mid B\mid\\\\\mid AB\mid=-3* 2=-6](https://img.qammunity.org/2020/formulas/mathematics/college/f2bmc19m4mbaarft56bluc72ri4iau8ue8.png)
b) det (B⁵ )
![\mid B^5\mid=\mid B\mid ^5=2^5=32](https://img.qammunity.org/2020/formulas/mathematics/college/4xkbjbf7ulud7jbmuyg4s4nf5nl9n8aqdx.png)
c) det (2A)
Since we know that
![\mid kA\mid =k^n\mid A\mid](https://img.qammunity.org/2020/formulas/mathematics/college/9p9vfuhvafgl3jtbbic62hxqwpd3nbytn4.png)
so, it becomes,
![\mid 2A\mid =2^4\mid A\mid=16* -3=-48](https://img.qammunity.org/2020/formulas/mathematics/college/9ryld2hahvagnqur8xva2a5lr0czczzgxh.png)
d)
![\bold{det(A^TA)}](https://img.qammunity.org/2020/formulas/mathematics/college/j9wovwdr9cfek753va6ioy68g3pxhvxdlc.png)
Since we know that
![\mid A^T\mid=\mid A\mid](https://img.qammunity.org/2020/formulas/mathematics/college/j5ds43dgurx209is2bjcqmc0tiegct7eyd.png)
so, it becomes,
![\mid A^TA\mid=\mid A^T\mid * \mid A\mid=-3* -3=9](https://img.qammunity.org/2020/formulas/mathematics/college/g4k3geafhu6y2wnc5ujsml4nzhp47ou73f.png)
e) det (B⁻¹AB)
As we know that
![\mid B^(-1)\mid =\mid B\mid](https://img.qammunity.org/2020/formulas/mathematics/college/iig4p0q3prgj3wd9kf8dlkk8vh0a6wn3lj.png)
so, it becomes,
![\mid B^(-1)AB}\mid =\mid B^(-1).\mid \mid A\mid.\mid B\mid=2* -3* 2=-12](https://img.qammunity.org/2020/formulas/mathematics/college/osq09ba6lhkzusnp9a1mf237u6xp9weun3.png)
Hence, a) -6, b) 32, c) -48, d) 9, e) -12